1991
DOI: 10.1210/jcem-72-3-588
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pattern of Urinary Epidermal Growth Factor in the Premature Infant and the Influence of Gender*

Abstract: We report the cross-sectional pattern of first day urinary epidermal growth factor/creatinine (EGF/Cr) levels in 159 appropriate for gestational age infants born at 26-41 weeks gestation. EGF/Cr levels rose significantly earlier in female infants than levels in male infants. In female infants levels were similar to term levels beginning at 30-32 weeks. Mean EGF/Cr levels in male infants were similar to term values beginning at 32-34 weeks. We could not demonstrate any influence from acute perinatal events on E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
2
9
1
Order By: Relevance
“…Our previous developmental study demonstrated significant gestational and postnatal age effects on EGF values but did not address changes during week 1 [8]. Weekly EGF concentrations spontaneously increased in infants who recovered from early lung disease.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our previous developmental study demonstrated significant gestational and postnatal age effects on EGF values but did not address changes during week 1 [8]. Weekly EGF concentrations spontaneously increased in infants who recovered from early lung disease.…”
Section: Discussionmentioning
confidence: 82%
“…Dexametha-sone therapy for CLD was associated with an increase in EGF concentrations. Our developmental studies demonstrated that increases in urinary EGF concentrations correlated to advancing gestational and postnatal age [8], but the factors which were important in determining the variability in EGF concentrations in week 1 were not defined. The possible role of EGF in gut development and disease was studied in infants with feeding intolerance or necrotizing enterocolitis where EGF values correlated with the severity of gut disease, and cessation of feedings decreased EGF values [9].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, Scott et al [4] demonstrated a significant nonlinear increase in urinary EGF/Cr ratio by 30–34 weeks of gestational age. Urinary EGF/Cr levels in those premature infants of gestational age 30–34 weeks were similar to the values of full-term neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Although still not clear, the role of EGF in renal development and maturation has been suggested. Several studies [3, 4, 5, 6] showed evidence of renal origin of urinary EGF in human neonates, developmental patterns of urinary EGF in premature infants, and decreased urinary EGF excretions in neonates with intrauterine growth retardation. In animal experiments, thyroid hormone can enhance renal EGF synthesis and thus increase urinary EGF excretion [7, 8, 9].…”
Section: Introductionmentioning
confidence: 99%